PENGARUH TAYANGAN UPIN DAN IPIN TERHADAP GAYA BERBAHASA SISWA SEKOLAH DASAR - Ira Anggraeni; Tesa Apriani; Aditya Permana (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This study aims to describe the influence of upin and ipin impressions on the style of language of elementary school students. This study is a qualitative descriptive method that interprets data relating to situations that occur, attitudes, and views that are symptomatic in the community and the influence on a condition. The data in this study is the style of language students, especially elements of Malay language in the conversation of students. Source of data obtained from conversations of elementary students. Based on the results of the analysis, found that the influence of upin and ipin impressions that can be known at the time of students to communicate in the school environment, students often imitate what is spoken by the character in the film. It is considered capable of influencing the development of the language.